A space on the side of the road : cultural poetics in an "other" America - Stewart, Kathleen, 1953- (Princeton University Press, 1996)
"A Space on the Side of the Road vividly evokes an 'other' America that survives precariously among the ruins of the West Virginia coal camps and 'hollers' ... [It] uses both language and photographs to help readers encounter a fragmented and betrayed community, one 'occupied' by schoolteachers, doctors, social workers, and other professionals representing an 'official' America."--Back cover